2007
DOI: 10.1242/jeb.005751
|View full text |Cite
|
Sign up to set email alerts
|

In ovotemperature manipulation influences embryonic motility and growth of limb tissues in the chick (Gallus gallus)

Abstract: SUMMARY The chick embryo, developing in the egg, is an ideal system in which to investigate the effects of incubation environment on the development of the embryo. We show that raising the temperature of the eggs by just one degree,from 37.5°C to 38.5°C, during embryonic days (ED) 4–7 causes profound changes in development. We demonstrate that embryonic movement is significantly increased in the chicks raised at 38.5°C both during the period in which they are at the higher temperature but also 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 49 publications
4
82
1
2
Order By: Relevance
“…There is either a direct effect by influencing molecular steps necessary for the proliferation and differentiation of myoblasts, or an indirect by general stimulation of the metabolism and the in-ovo movement of the embryo, as postulated by Hammond et al (2007). The present results showing no difference of the broiler growth and slaughter characteristics are difficult to discuss because already published investigations differed in the analysed poultry species, the treatment conditions and the time of sampling.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…There is either a direct effect by influencing molecular steps necessary for the proliferation and differentiation of myoblasts, or an indirect by general stimulation of the metabolism and the in-ovo movement of the embryo, as postulated by Hammond et al (2007). The present results showing no difference of the broiler growth and slaughter characteristics are difficult to discuss because already published investigations differed in the analysed poultry species, the treatment conditions and the time of sampling.…”
Section: Discussionmentioning
confidence: 52%
“…Other publications that increased the incubation temperature at a similar period during embryogenesis disagree with the present results. Maltby et al (2004), Yahav et al (2004a and Hammond et al (2007) showed that the increased temperature has an positive effect on the post-hatch muscle development (e.g. BW or MFN).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A regime of 38.58C caused an increased myonuclear and fibre number in ST, along with a delay in differentiation (Maltby et al, 2004). In chickens, Hammond et al (2007) have shown that Rehfeldt, Te Pas, Wimmers, Brameld, Nissen, Berri, Valente, Power, Picard, Stickland and Oksbjerg these small temperature manipulations alter muscle cellularity, possibly through an effect on in ovo movement activities (higher temperatures produced sustained increases in movement). Werner and Wicke (2008) reported that increased temperature (38.58C) between embryonic days 7 and 10 of incubation positively influenced the post-hatch muscle development in cocks, but not in hens.…”
Section: Consequences Of Maternal Nutritionmentioning
confidence: 97%